Complementary Therapies for the Contemporary Healthcare - Saad, Marcelo; de Medeiros, Roberta (IntechOpen, 2012)
Complementary therapies (CTs) are practices, products or systems for health that are outside the domain of conventional medicine (also called Western or allopathic medicine), used either to treat illnesses or to promote health and well-being. Defining CTs is difficult, because the field is very broad and constantly changing. The list of what is considered CT changes continually, and therapies whose safety and effectiveness are demonstrated may become part of conventional medicine. We hope the information from the present book can collaborate in some manner with the ongoing process of evolution of the paradigms related to concepts of health, disease and healing.